The Immutability of Personal Status Law - Soliman, Leena (AUC Knowledge Fountain, 2022)
Personal Status laws in Egypt were first coded in 1920 and were slightly amended throughout time. They were based on religious texts, and hence, are treated as words and teachings of God. Thus, the amendments that were developed throughout history were a result of different interpretations. Throughout the twentieth century, personal status laws in Egypt were enacted by the Egyptian state to build marriage as a more permanent bond as intended by traditional Islamic jurisprudence. Providing women with more marital rights, including more grounds for judicial divorce, was believed to strengthen the marital bond. This paper will trace the insight of different legal domains and developments over time and how these laws are interpreted as Sharia rather than Fiqh. This thesis attempts to highlight the distinction between Fiqhand Sharia by addressing the application of Islamic Sharia in Egypt and the textual sharia rules and teachings on personal status matters.